1999
DOI: 10.1038/sj.onc.1203179
|View full text |Cite
|
Sign up to set email alerts
|

Dual G1 and G2/M phase inhibition by SC-ααδ9, a combinatorially derived Cdc25 phosphatase inhibitor

Abstract: The Cdc25 dual speci®city phosphatase family has a central role in controlling cell cycle progression and has been implicated in the etiology of cancer. One compound, 4-(benzyl-(2-[(2, 5-diphenyl-oxazole-4-carbonyl)-amino]-ethyl)-carbamoyl)-2-decanoylamino butyric acid (SC-aad9), was previously identi®ed as the most potent reported synthetic inhibitor of Cdc25 phosphatases in vitro. In the present study, we demonstrate that SC-aad9 inhibited Cdc25-dependent cell cycle progression at both G1 and G2/M phase usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Cdc25A and Cdc25B have also been shown to be overexpressed in several types of cancer cells (43)(44)(45)(46)(47)(48)(49)(50). Importantly, it has also been shown that treatment of tumor cell lines with Cdc25 inhibitors inhibits tumor growth or causes cell cycle arrest (15,16,(51)(52)(53), which validates Cdc25 as a drug target and makes inhibitors of Cdc25 very valuable. It has been known for some time that suramin treatment increases the tyrosine phosphorylation levels of Cdc2, a cyclin-dependent kinase responsible for initiation of mitosis (54).…”
Section: Resultsmentioning
confidence: 96%
“…Cdc25A and Cdc25B have also been shown to be overexpressed in several types of cancer cells (43)(44)(45)(46)(47)(48)(49)(50). Importantly, it has also been shown that treatment of tumor cell lines with Cdc25 inhibitors inhibits tumor growth or causes cell cycle arrest (15,16,(51)(52)(53), which validates Cdc25 as a drug target and makes inhibitors of Cdc25 very valuable. It has been known for some time that suramin treatment increases the tyrosine phosphorylation levels of Cdc2, a cyclin-dependent kinase responsible for initiation of mitosis (54).…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, the antiproliferative effect of D609 can hardly be regarded as specific for HER2-overexpressing cells, because previous studies in our laboratory showed that cell exposure to this xanthate is able to induce cell-cycle arrest in G 0 /G 1 in different types of cells, such as HER2-non-overexpressing ovary cancer cells and mitogen-stimulated fibroblasts [39,40]. Further studies are needed to investigate whether and to what extent the antiproliferative effect of D609, similar to that of another PC-PLC inhibitor, SC-ααδ9 (4-(benzyl-(2- [(2,5-diphenyoxazole-4-carbonyl)amino]ethyl)carbamoyl)-2-decanolaminobutyric acid), is linked to the phosphorylation or inhibition or both of selective cyclin-dependent kinase activities [62]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, SC-aad9 is a competitive inhibitor of all 3 human Cdc25 isoforms in vitro with low mM K i values (Rice et al, 1997). SCaad9 also inhibits cell cycle progression at both the G1 and G2/M phases in synchronized murine mammary carcinoma cells, causes enhanced tyrosine phosphorylation of cdk1, cdk2 and cdk4 and, decreases cdk4 kinase activity (Tamura et al, 1999). A limited structureactivity study indicated the critical importance of a lipophilic nonyl-residue on SC-aad9 presumably due to interactions with a conserved hydrophobic region adjacent to the catalytic site.…”
Section: Small Molecule Inhibitors Of Cdc25mentioning
confidence: 99%